Assessing Contributions of Major Emitters' Paris‐Era Decisions to Future Temperature Extremes. Issue 7 (4th April 2019) - Lewis, Sophie C.; Perkins‐Kirkpatrick, Sarah E.; Althor, Glenn; King, Andrew D.; Kemp, Luke
Abstract: The likelihood and severity of high‐impact future temperature extremes can be reduced through climate change mitigation efforts. However, meeting the Paris Agreement warming limits requires notably stronger greenhouse gas emissions reduction efforts by major emitters than existing pledges. We examine the impact of Paris‐era decision‐making by the world's three largest greenhouse gas emitters (EU, USA, and China) on projected future extreme temperature events. Country‐level contributions to the occurrence of future temperature extremes are calculated based on current emissions policies and sequential mitigation efforts, using a new metric called the Contribution to Excess Risk Ratio. We demonstrate the Contribution concept by applying it to extreme monthly temperature projections. In many regions, future extremes depend on the current and future carbon dioxide emissions reductions adopted by major emitters. By implementing stronger Paris‐era climate pledges, major emitters can reduce the frequency of future extremes and their own calculated contributions to these temperature extremes. Plain English Summary: Temperature extremes can damage aspects of human society, infrastructure, and our ecosystems. The frequency, severity, and duration of high temperatures are increasing in some regions and are projected to continue increasing with further global temperature increases as greenhouse gas emissions rise. While the international Paris Agreement aims to limit warming through emissions reduction pledges, none of the major emitters has made commitments that are aligned with limiting warming to 2 °C. In this analysis, we examine the impact of the world's three largest greenhouse gas emitters' (EU, USA, and China) current and future decisions about carbon dioxide emissions on the occurrence of future extreme temperatures. We show that future extremes depend on the emissions decisions made by the major emitters. By implementing stronger climate pledges, major emitters can reduce the frequency of future extremes and their own calculated contributions to these temperature extremes. Key Points: The contribution of major greenhouse gas emitters to future temperature extremes is calculated Projected future extremes depend on current and near‐future CO2 emissions trajectories of the major emitters Major emitters' calculated contributions to future temperature extremes is reduced through emissions mitigation